A Bibliometric Analysis on Authoritarian Parenting Style Research in the Period 2018 to 2023 - Tenribali, Dewani; Nur, Haerani (Indonesian Journal of Librarianship, 2023)
Abstract Background/Problem Statement : Research on authoritarian parenting style revealed that subjectivity and inability to define measurement methods had emerged as constraints, that had brought a lack of literature discussing the authoritarian parenting style. By examining this topic, various research opportunities are obtained that can be developed to cover the gaps in existing research and studies . Purpose : to analyze the challenges of literature review on the theme of authoritarian parenting and to describe several research development opportunities that can be carried out on the topic of authoritarian parenting style . Method : This literature review used bibliometric analysis from previous research data sources and review articles in the period 2018 to 2023. Result : Various studies that have been published since 2018 show various challenges faced by research on Authoritarian Parenting Style because this topic is a sensitive topic , using measurement influenced by subjective factors and challenges stemming from cultural considerations. By paying close attention to these challenges, several research development opportunities in the future must be built using a collaborative (interdisciplinary) approach with other scientific fields, so that it is possible to obtain some research results that are new and different from previous research. Conclusion : The subjective factor is the dominant cause of the limitations in carrying out research on authoritarian parenting. Therefore, it is necessary to develop research by conducting interdisciplinary research with other scientific fields . Keywords: Parenting; Authoritarian Parenting Style; Bibliometric Analyzing